VILLAGE GOVERNMENT MANAGEMENT ON THE EFFECTIVENESS OF ACHIEVING THE VILLAGE AUTONOMY PROGRAM THROUGH THE PERFORMANCE OF VILLAGE APPARATUSES IN GARUT REGENCY - Muchtar, Muchtar; Hadita, Akmala; Hermana, Dody; Wufron, Wufron (Natapraja, 2023)
The village apparatus in the Garut Regency still needs to be fixed. It is suspected that the village autonomy program will be less successful because the management of village governance has yet to be implemented. This study intends to examine the influence of village government management on the effectiveness of regional apparatus in implementing the village autonomy program. Utilizing a survey approach, quantitative and descriptive analysis is the research methodology used. The research target group was 421 villages included in the village administration in Garut Regency, with 81 villages being the sample of 81 respondents. Statistical analysis method using path analysis is the applied data analysis technique. Based on the discussion results, the village government's management needs to disseminate development to the community optimally. The performance of the village apparatus could have been better for the independence of the apparatus in carrying out its duties and responsibilities and the effectiveness of the achievement of the village autonomy program. The findings of the research results are suggested to the government of Garut Regency to increase the effectiveness of achieving the village autonomy program to make clear and detailed village strategic policy formulations.